2018
DOI: 10.18203/2349-2902.isj20180837
|View full text |Cite
|
Sign up to set email alerts
|

Predicting difficult laparoscopic cholecystectomy

Abstract: Background: Laparoscopic cholecystectomy (LC) has become the gold standard treatment for gallstone disease. Though mostly safe occasionally it can be difficult due to various problems faced during surgical procedure. Anticipation of likely difficulty can help in avoiding complications. Methods: With the aim of identifying various predictors of difficulty and their correlation with likely difficulty this prospective study on 50 adults undergoing laparoscopic cholecystectomy for symptomatic cholelithiasis was un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
2
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 16 publications
(18 reference statements)
3
14
2
3
Order By: Relevance
“…11 Vivek et al described similar results when they reported the role of increasing age, male gender, high BMI, previous biliary disease, previous surgery, and preoperative sonological findings in accurately predicting the intra operative difficulties of laparoscopic cholecystectomy. 12 Similar results were also obtained by Gupta et al and Kulkarni et al 13,14 The study found the scoring system developed by Randhawa and Pujari et al to have a sensitivity of 77.8%, specificity of 78.1%, positive predictive value of 66.7% and a negative predictive value of 86.2% in the prediction of difficult laparoscopic cholecystectomies. However, Randhawa and Pujari et al reported a sensitivity and specificity of 75.00% and 90.24%, respectively.…”
Section: Discussionsupporting
confidence: 61%
“…11 Vivek et al described similar results when they reported the role of increasing age, male gender, high BMI, previous biliary disease, previous surgery, and preoperative sonological findings in accurately predicting the intra operative difficulties of laparoscopic cholecystectomy. 12 Similar results were also obtained by Gupta et al and Kulkarni et al 13,14 The study found the scoring system developed by Randhawa and Pujari et al to have a sensitivity of 77.8%, specificity of 78.1%, positive predictive value of 66.7% and a negative predictive value of 86.2% in the prediction of difficult laparoscopic cholecystectomies. However, Randhawa and Pujari et al reported a sensitivity and specificity of 75.00% and 90.24%, respectively.…”
Section: Discussionsupporting
confidence: 61%
“…[10][11][12] Some authors have reported no significant relation between gall bladder wall thickness and a difficult laparoscopic cholecystectomy whilst others have reported it to be significant. 8,13 Present study found this relation to be statistically significant.…”
Section: Discussionmentioning
confidence: 45%
“…These findings are consistent with other studies conducted by various authors. [8][9][10] A significant relation was found by us between previous attacks of acute cholesystitis and intra-operative difficulty during laparoscopic cholecystectomy. Similar findings have been corraborated by various authors in litreature.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Spillage of gallbladder contents during LC has been extensively explained as a factor for the conversion of LC to open surgery and difficult LCs. [ 26 27 28 ] Even, Rice et al . have presented an increased risk of postlaparoscopic intra-abdominal abscess formation.…”
Section: Discussionmentioning
confidence: 99%